Khảo sát khả năng tích lũy đồng từ đất trồng và nguy cơ rủi ro sức khỏe khi sử dụng một số loại thảo mộc trồng trên đất ô nhiễm - Lê, Thị Thanh Trân (2024)
In this study, the accumulation levels of copper in the biomass of certain herbs, including oregano, celery, gotu kola, and purple perilla when grown on contaminated copper soil, were investigated. The results showed that copper had the potential to accumulate in plants, with the highest accumulation in the roots, decreasing in the stems and leaves. When grown in copper contaminated soil ranging from 50 to 1500 ppm, the accumulation of copper decreased in the following order: oregano roots (8.28 ÷ 103.05 ppm) > purple perilla roots (8.14 ÷ 66.98 ppm) > gotu kola roots (6.10 ÷ 39.95 ppm) > celery roots (5.40 ÷ 31.74 ppm) > oregano stems + leaves (2.59 ÷ 24.02 ppm) > purple perilla stems + leaves (3.56 ÷ 16.45 ppm) > gotu kola stems + leaves (3.62 ÷ 16.74 ppm) > celery stems + leaves (1.75 ÷ 7.16 ppm). Health risk indices for adults and children when using these herbs were also assessed. The THQs (Target Hazard Quotients) for copper increased in the following order: celery < purple perilla < oregano < gotu kola, and THQs for children were higher than those for adults.